Analysis of the performance of manufacturing companies before and after the merger on the Indonesian stock exchange in the period 2002-2006. - Rista Adiningrum (Institute of Accounting Research and Novation (IARN), 2021)
The purposes of this research are to gain evidence whether mergers gave positive effects on manufacturing company's financial performance and to evaluate each of the manufacturing sub-sectors' financial performance, in what sub-sectors did the merger create the best performance. The population in this research is a merged manufacturing company that is listed in IDX. The method of sample selection is purposive sampling method. This research used secondary data that is audited companies' financial report. The data processing technique in this research is descriptive statistics and paired sample tests. The result of this research is that they have no evidence that the company's financial performance has improved after merger based on liquidity, activity, solvency and profitability ratios. stone, clay,